Role of sphingosine 1-phosphate (S1P) in sepsis-associated intestinal injury - Sun, Gehui; Wang, Bin; Zhu, Hongquan; Ye, Junming; Liu, Xiaofeng (Frontiers in Medicine, 2023)
Sphingosine-1-phosphate (S1P) is a widespread lipid signaling molecule that binds to five sphingosine-1-phosphate receptors (S1PRs) to regulate downstream signaling pathways. Sepsis can cause intestinal injury and intestinal injury can aggravate sepsis. Thus, intestinal injury and sepsis are mutually interdependent. S1P is more abundant in intestinal tissues as compared to other tissues, exerts anti-inflammatory effects, promotes immune cell trafficking, and protects the intestinal barrier. Despite the clinical importance of S1P in inflammation, with a very well-defined mechanism in inflammatory bowel disease, their role in sepsis-induced intestinal injury has been relatively unexplored. In addition to regulating lymphocyte exit, the S1P-S1PR pathway has been implicated in the gut microbiota, intestinal epithelial cells (IECs), and immune cells in the lamina propria. This review mainly elaborates on the physiological role of S1P in sepsis, focusing on intestinal injury. We introduce the generation and metabolism of S1P, emphasize the maintenance of intestinal barrier homeostasis in sepsis, and the protective effect of S1P in the intestine. We also review the link between sepsis-induced intestinal injury and S1P-S1PRs signaling, as well as the underlying mechanisms of action. Finally, we discuss how S1PRs affect intestinal function and become targets for future drug development to improve the translational capacity of preclinical studies to the clinic.